Addressing isolation: the importance of integration and the role of institutions. (9th March 2015) - Yates, Jonathan
Abstract : Purpose: – The purpose of this paper is to highlight the importance of integration in tackling isolation in later life, propose institutions as a key factor in forming intergenerational friendships, and assess the key conditions which need to be established. Design/methodology/approach: – Assessment based on work on social contact theory by Professor Miles Hewstone, amongst others, as well as case studies, research from Age UK and the Social Integration Commission. Findings: – Isolation can be seen as part of the broader issue of a failure of social integration. A lack of integration in earlier life results in networks which are not age-diverse. This results in isolation in later life. Institutions are key in preventing this, as they allow for the formation of intergenerational friendships and trust. Originality/value: – Based on an article by the author (www.demos.co.uk/publications/mapping integration), age-specific integration is reviewed, and supplementary research considered.